Adsorption and recovery characteristics of phosphorylated sawdust bead for indium(III) in industrial wastewater - Jeon, Choong; Cha, Ju-Hyun; Choi, Jae-Young (ELSEVIER SCIENCE INC, 2015)
Powdered phosphorylated sawdust was immobilized as bead form to apply to the adsorption and recovery of indium(III) from industrial wastewater. Swelling of beads, channeling of flow and the increase of pressure drop were not observed through column operations. The maximum adsorption capacity using Langmuir isotherm model was 1.121 mg/g. The breakthrough point for indium(III) was appeared around 25(1.0 mL/min) and 42 bed volumes (0.5 mL/min), respectively and indium(III) bound to the beads was readily desorbed and recovered by a few bed volumes of 0.5 M of HCl solution. Furthermore, breakthrough point of indium(III) for secondly reused beads can be still maintained as about 39. (C) 2015 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: AQUEOUS-SOLUTION; ALGINIC ACID; CESIUM ION; REMOVAL; THERMODYNAMICS; KINETICS; BEHAVIOR; SERICITE; RESINS